Canvas support impregnation materials and techniques: a study of Portuguese painting and its conservation issues - Andréa Carolina Teixeira (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This paper focuses on the study of oil based coating impregnations, applied in the past, on the reverse of Portuguese painting canvas supports.The scientific study of the impregnation materials found in the painting “The Knight of the Order of Malta” (18th century) was carried out on samples using several analytical techniques – Optical Microscopy (OM) under visible reflected and polarised light and ultraviolet fluorescence (UV); Gas chromatography mass spectrometry (GC-MS), Fourier transform Infrared spectroscopy (transmission and FTIR-ATR), and Scanning electron microscopy coupled with an energy dispersive X-ray spectroscopy (SEM-EDX) – in order to identify the materials and the techniques used in this practice.